Biodiesel production from Cascabela ovata seed oil. (September 2019) - Sánchez-Arreola, Eugenio; Bach, Horacio; Hernández, Luis R.
Abstract: Due to near exhaustion of world oil reserves and increasing environmental concerns, there is a demand for alternatives to fossil fuels. Biodiesel production from renewable sources is considered a candidate for substitution of petrodiesel. Cascabela ovata is a plant that grows in poor soils with limited water precipitation and it is circumscribed to the arid parts of Mexico. C. ovata seeds are rich in oil with applications in the production of biodiesel. Physicochemical properties of this oil were evaluated according to AOCS and ASTM methods. The profile of the fatty acids was determined by gas chromatography. Fuel properties were determined using the ASTM methods. Results showed that the main fatty acids in the oil mixture were oleic acid, palmitic acid, and stearic acid. The best transesterification yield obtained was 95% under alkaline reaction using methanol and the fuel properties are within the limits of petrodiesel standards. Graphical abstract: Unlabelled Image Highlights: Seeds from Cascabela ovata were used for oil and biodiesel production. C. ovata oil properties demonstrated that it can be used for biodiesel production. The fatty acid profile was analyzed by gas chromatography and confirmed by NMR. Transesterification yield of 95% was obtained with MeOH under alkaline conditions. The properties of the C. ovata biodiesel conform to the ASTM and European standards.